Rv2031c of Mycobacterium tuberculosis: a master regulator of Rv2028–Rv2031 (HspX) operon - Mushtaq, Khurram; Sheikh, Javaid A.; Amir, Mohammed; Khan, Nargis; Singh, Balvinder; Agrewala, Javed N. (Frontiers in Microbiology, 2015)
Abstract Genes belonging to the same operon are transcribed as a single mRNA molecule in all prokaryotes. The genes of the same operon are presumed to be involved in similar metabolic and physiological processes. Hence, computational analysis of constituent proteins could provide important clues to the functional relationships within the operonic genes. This tends to be more fruitful in the case of Mycobacterium tuberculosis (Mtb), considering the number of hypothetical genes with unknown functions and interacting partners. Dramatic advances in the past decade have increased our knowledge of the mechanisms that tubercle bacilli employ to survive within the host. But the phenomenon of Mtb latency continues to baffle all. Rv2031c belonging to dormancy regulon of Mtb is predominantly expressed during latency, with myriad immunological roles. Thus we attempted to analyze the operon comprising Rv2031c protein to gain insights into its role during latency. In the current study, we have carried out computational analysis of proteins encoded by genes known to be a part of this operon. Our study includes phylogenetic analysis, modeling of protein 3D structures, and protein interaction network analysis. We describe the mechanistic role in the establishment of latency and regulation of DevS/DevR component system. Additionally, we have identified the probable role of these proteins in carbohydrate metabolism, erythromycin tolerance and nucleotide synthesis. Hence, these proteins can modulate the metabolism of mycobacterium inside the host cells and can be important for its survival in latency. The functional characterization and interactome of this important operon can give insight into its role during latency along with the exploitation of constituent proteins as drug targets and vaccine candidates.